Representasi Maskulin Jokowi Pada #JKWVLOG Tinju Dalam Analisis Semiotika Roland Barthes - Lymbarski Caesariano; Yulianti Fajar Wulandari; Murtiadi Murtiadi; Yan Bastian (Brand Communication, 2022)
The purpose of this research is to find out the symbols that appear on a video blog or vlog. In this study, a video blog or vlog becomes the object of research. Video blog (vlog) featuring boxing with the concept of imaging an adult male figure with a masculine appearance. President Joko Widodo or Jokowi is one of the vloggers. In the video blog (vlog) he made with the title of the blog entitled "#JKWVLOG TINJU" it shows a figure who is far from the symbol of the presidency. This is what researchers are interested in analyzing from the semiotic side of Roland Barthes. The aim is to find out how the symbol of masculinity is raised by President Jokowi through his vlog content. This research uses constructivism paradigm, with this research approach using descriptive qualitative method. In this study, data were collected through thorough observations on the object of research, namely a vlog entitled "#JKWVLOG TINJU" as a knife of analysis by researchers using Roland Barthes' semiotics model, namely an analysis of sign relationships. The results showed that the representation of masculinity was no sissy stuff, Give them Hell, Be a Big Wheel, and Be a Sturdy Oak